Analisis Pemahaman Siswa SMA Mengenai Ilmu Bioteknologi di Kelas XII Di MAS Al-Manar Pulo Raja - Dayana Fazira; Ayu Fitri Jumain; Erna Suyanti; Masdelina Sipahutar; Miftahul Khairani,M.Pd; Indayana Febriani Tanjung,M.Pd (Symbiotic: Journal of Biological Education and Science, 2022)
ABSTRACT The purpose of this research is to analyze students' understanding in biology learning, especially in biotechnology learning at the high school level. The methodology in this research is descriptive analysis with data collection techniques using tests, field notes and interviews. The population and the sample used are high school students of class XII at MAS AL-MANAR Pulo Raja, with a total of 20 people. The results of this study get students' understanding in the medium category.